How can inhabited institutionalism inform the analysis of medical education?. Issue 12 (12th July 2021) - Gulasaryan, Aleksandra; Aitken, Gillian; Fawns, Tim; Jones, Derek; Napier, Jordan; Walker, Kim
Abstract: Context: Medical schools are complex organisations existing at the intersection of higher education and healthcare services. This complexity is compounded by many competing pressures and drivers from professional and regulatory bodies, the wider political environment and public expectations, producing a range of challenges for those involved in all stages of medical education. There are established approaches that have been used to address research questions related to these challenges; some focus on organisational structures, characteristics and performance; others on the interactions that take place in a particular setting. Less common are approaches that integrate data on macro‐level structures with the micro‐level interactions of the people who inhabit those structures. Looking at the interaction of the macro and the micro opens up possibilities for the new insights. Framework: We propose using an approach with roots in social theory—Inhabited Institutionalism (II)—that is largely unexplored in medical education. II has been described as Janus‐faced, looking both outwards, at the broader context of medical education, and inwards, at the ways in which meanings are constructed and re‐constructed by participants within a particular setting. Methods: After describing the theoretical framework of II, we explain how it can be used to understand medical education as subject to both broader societal structures (the macro level) and interactions between people (the micro level), as well as—crucially—their mutual influence. Conclusion: II offers the opportunity to combine macro‐ and micro‐level perspectives, leading to a more expansive understanding of the operation of medical education which sees its form and function as neither entirely determined by structures nor a construction of individuals engaged in it. In doing so, it potentially offers a valuable way of considering the intractable problem of how to successfully manage change, offering a combined top‐down and bottom‐up perspective. Abstract : Gulasaryan et al. explore the concept of inhabited institutionalism as a domain of study that can offer medical education nuanced understanding of how local practices are shaped by wider institutional pressures and educators' responses.